Dinâmica da informalidade no mercado de trabalho brasileiro: 1993 - 2009. - Vasconcelos, Emanuelle Aléxia Santos de (2012)
Historically, the higher informality has been one of the structural characteristics of the Brazilian labour market. Since 1990, in a context of the labour market disruption, informality reaches its highest levels, being revisited with more emphasis on the academy. The aim of this work is to investigate the dynamics of informality in the Brazilian labour market between 1993 and 2009, from the perspective of the dynamism of economic growth. The debate on the subject does not come to a consensus, which gives the literature a controversial way to present the theme. Thus, the literature review was based on the approach of some conceptions of informality, emphasizing the great debate that surrounds the theme. The referring data for the Brazilian labour market informality was originated from the National Household Sample Survey (PNAD) microdata which indicated that in a context of low economic dynamism during the 90s, despite of its high proportions, the level of informality remained virtually unchanged throughout the decade, which contradicts the results presented by the national literature. In the 2000s in a context of economic recovery, informality levels showed considerable reduction. However, despite this result there still exist a huge number of informal labourers within poor working conditions, which mainly affects the poorest classes of the society, women, non-whites, individuals residing in rural area and low schooling.